Rancang Bangun E-Commerce Hewan Ternak Berbasis Android: Design and Development of Android-Based Livestock E-Commerce - Brilly Cruiser Keles; Arthur Mourits Rumagit; Heilbert Armando Mapaly (Universitas Sam Ratulangi, 2025)
Abstract — The limitation of dedicated e-commerce platforms specifically designed for livestock trading has resulted in a complex and inefficient transaction process. In order to achieve this goal, this research applies software development methodology using the Waterfall approach, involving stages such as needs analysis, interface design, application development using the Kotlin programming language, and testing of the application's functionality and reliability. The research findings indicate that the developed livestock e-commerce application facilitates farmers in selling livestock products online, providing ease in the ordering process, and ensuring the reliability and authenticity of information conveyed to consumers. The competitive advantage of this application lies in providing comprehensive information and userfriendly features. Through the implementation of this application, it is expected to contribute to an increase in economic value for farmers by expanding market access and reducing dependence on conventional distribution channels. Positive impacts will also be experienced by consumers who can easily access information about livestock and conduct transactions online. Key words — Android; E-Commerce; Livestock; Mobile Abstrak — Keterbatasan keberadaan platform e-commerce yang secara khusus didedikasikan untuk perdagangan hewan ternak, menyebabkan proses transaksi yang kompleks dan tidak efisien. Dalam rangka mencapai tujuan ini, penelitian ini menerapkan metode pengembangan perangkat lunak menggunakan pendekatan Waterfall, yang melibatkan tahap analisis kebutuhan, perancangan antarmuka, pengembangan aplikasi dengan bahasa pemrograman Kotlin, dan uji coba fungsionalitas serta kehandalan aplikasi. Hasil penelitian menunjukkan bahwa aplikasi e-commerce yang dikembangkan memfasilitasi peternak dalam menjual produk hasil ternak secara online, memberikan kemudahan proses pemesanan, dan menjamin keandalan serta keaslian informasi yang disampaikan kepada konsumen. Keunggulan kompetitif aplikasi ini terletak pada penyediaan informasi yang komprehensif dan kemudahan penggunaan. Dengan penerapan aplikasi ini, diharapkan terjadi peningkatan nilai ekonomi bagi peternak melalui perluasan akses pasar dan pengurangan ketergantungan pada saluran distribusi konvensional. Dampak positif juga akan dirasakan oleh konsumen yang dapat mengakses informasi tentang hewan ternak dengan mudah dan melakukan transaksi secara online. Kata kunci — Android; E-Commerce; Hewan ternak; Mobile